Take one step backward to move forward: Assessment of genetic diversity and population structure of captive Asian woolly-necked storks (Ciconia episcopus) - Jangtarwan, Kornsuang (PLoS One, 2019)
The fragmentation of habitats and hunting have impacted the Asian woolly-necked stork (Ciconia episcopus), leading to a serious risk of extinction in Thailand. Programs of active captive breeding, together with careful genetic monitoring, can play an important role in facilitating the creation of source populations with genetic variability to aid the recovery of endangered species. Here, the genetic diversity and population structure of 86 Asian woolly-necked storks from three captive breeding programs [Khao Kheow Open Zoo (KKOZ) comprising 68 individuals, Nakhon Ratchasima Zoo (NRZ) comprising 16 individuals, and Dusit Zoo (DSZ) comprising 2 individuals] were analyzed using 13 microsatellite loci, to aid effective conservation management. Inbreeding and an extremely low effective population size (N(e)) were found in the KKOZ population, suggesting that deleterious genetic issues had resulted from multiple generations held in captivity. By contrast, a recent demographic bottleneck was observed in the population at NRZ, where the ratio of N(e) to abundance (N) was greater than 1. Clustering analysis also showed that one subdivision of the KKOZ population shared allelic variability with the NRZ population. This suggests that genetic drift, with a possible recent and mixed origin, occurred in the initial NRZ population, indicating historical transfer between captivities. These captive stork populations require improved genetic variability and a greater population size, which could be achieved by choosing low-related individuals for future transfers to increase the adaptive potential of reintroduced populations. Forward-in-time simulations such as those described herein constitute the first step in establishing an appropriate source population using a scientifically managed perspective for an in situ and ex situ conservation program in Thailand.